Transient simulation of pulsed purge film cooling on flow and thermal characteristics of a turbine endwall. (October 2019) - Liu, Youhong; Luo, Yifu
Highlights: We numerically investigate the cooling effect of slot pulsed purge flow on turbine endwall. The influence of slot orientation angle is studied. The influence of mass flow ratio of cooling gas is studied. The effect of Strouhal number on endwall thermal characteristics is discussed. Abstract: This paper presents influence investigation of pulsed purge film on flow and thermal characteristics of a turbine endwall. Three-dimensional transient Reynolds-averaged Navier-Stokes equations coupled with SST k  −  ω turbulence model are utilized in this study. Varied slot orientation angles α, mass flow ratios (MFR) and Strouhal ( St ) numbers are selected as research parameters. The results indicate that endwall film cooling effectiveness varies as orientation angle α increases. Optimum film cooling effectiveness is obtained at α  = 45° for cosine wave injection. MFR increases the level of film cooling effectiveness throughout the cascade channel. At the same MFR, square wave injection has the worst cooling effect. In a time period, instantaneous film cooling effectiveness changes drastically. The distribution of the instantaneous film cooling effectiveness is affected by St number and cooling outflow pattern. As St increases, the laterally-averaged film cooling effectiveness changes differently for cosine and square waves in the whole cascade channel.